Old stuff still trending: use of propafenone as a safety net until catheter ablation in a patient with documented pre-excited atrial fibrillation and Wolff–Parkinson–White syndrome – a classic case report. Issue 12 (30th November 2021) - Karelas, Dimitrios; Papanikolaou, John; Kossyvakis, Charalampos; Platogiannis, Dimitrios
Abstract: Background: Atrial fibrillation in Wolff– Parkinson– White syndrome may result in life-threateningly rapid antegrade conduction over a bypass tract, manifested by an irregular broad-complex (pre-excited) tachycardia that can degenerate to ventricular fibrillation. The shortest pre-excited RR interval below 250 ms during atrial fibrillation (AF) predicts increased risk of sudden cardiac death. Case summary: We report a case of a 43-year-old man with unremarkable cardiac history who presented due to sudden-onset feeling of palpitations and pre-syncope after strenuous lifting. Electrocardiography depicted fast pre-excited AF. The shortest pre-excited RR interval was estimated at 160 ms, indicating an accessory pathway (AP) with short antegrade refractory period at risk for mediating sudden cardiac death. Direct current cardioversion restored sinus rhythm unravelling delta waves. The patient was put on propafenone 450 mg/day having an uneventful clinical course. On Day 10 post-admission, electrophysiological study induced rapid AF but the shortest pre-excited RR interval was substantially increased to 264 ms. A left anterolateral AP was ablated. The patient remained symptom free until his latest follow-up in the 3rd-month post-ablation without manifest pre-excitation on the surface electrocardiogram. Discussion: Treatment options of pre-excited AF include anti-arrhythmic agents but mainly electrical cardioversion. Cardioversion can safely restore sinus rhythm, while use of anti-arrhythmics often requires intensive care unit monitoring due to the risk of QT prolongation. Catheter ablation is the mainstay of therapy for symptomatic patients. Our rare report highlights the direct impact of propafenone on prolonging the refractoriness of the AP, effectively and safely, and reappraises propafenone's worthiness as a protective measure following pre-excited AF episode until ablation.